2016
DOI: 10.1371/journal.pone.0146994
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Uridine Administration Induces Fatty Liver and Pre-Diabetic Conditions in Mice

Abstract: Uridine is a pyrimidine nucleoside that exerts restorative functions in tissues under stress. Short-term co-administration of uridine with multiple unrelated drugs prevents drug-induced liver lipid accumulation. Uridine has the ability to modulate liver metabolism; however, the precise mechanism has not been delineated. In this study, long-term effects of uridine on liver metabolism were examined in both HepG2 cell cultures and C57BL/6J mice. We report that uridine administration was associated with O-GlcNAc m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
52
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 37 publications
3
52
2
Order By: Relevance
“…We previously reported the existence of a UDP-uridine loop in which hypothalamic UDP contents are increased in obesity as a direct consequence of elevated uridine supply from the periphery (Steculorum et al, 2015b). Consistent with this model, chronic uridine supplementation in mice leads to glucose intolerance associated with decreased insulin signaling in liver and increase hepatic gluconeogenesis (Urasaki et al, 2016). These data in conjunction with the results of the present study suggest that increased hypothalamic UDP levels, as a result of elevated peripheral supply of uridine, directly act on AgRP neurons to control hepatic insulin sensitivity and to deteriorate systemic insulin sensitivity and glucose homeostasis.…”
Section: Discussionsupporting
confidence: 54%
“…We previously reported the existence of a UDP-uridine loop in which hypothalamic UDP contents are increased in obesity as a direct consequence of elevated uridine supply from the periphery (Steculorum et al, 2015b). Consistent with this model, chronic uridine supplementation in mice leads to glucose intolerance associated with decreased insulin signaling in liver and increase hepatic gluconeogenesis (Urasaki et al, 2016). These data in conjunction with the results of the present study suggest that increased hypothalamic UDP levels, as a result of elevated peripheral supply of uridine, directly act on AgRP neurons to control hepatic insulin sensitivity and to deteriorate systemic insulin sensitivity and glucose homeostasis.…”
Section: Discussionsupporting
confidence: 54%
“…Uridine, a necessary pyrimidine nucleotide for RNA synthesis, can be synthesized de novo in mammals [1][2][3]. Uridine has been widely used in reducing cytotoxicity [4] and improving neurophysiological functions [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…As the metabolic product of UMP, uridine (UR) exerts restorative functions in tissues under stress . It has been reported that supplementation with fish oil and UR supports the intestinal physical barrier via up‐regulating of the ZO‐1 level .…”
Section: Introductionmentioning
confidence: 99%
“…10 As the metabolic product of UMP, uridine (UR) exerts restorative functions in tissues under stress. 11 It has been reported that supplementation with fish oil and UR supports the intestinal physical barrier via up-regulating of the ZO-1 level. 12 Intra-colonic administration of UR effectively prevented the development and progression of the dextran sulfate sodium (DSS) induced colitis symptoms in mice.…”
Section: Introductionmentioning
confidence: 99%